Dual-Band Multi-Layer Antenna Array with Circular Polarization and Gain Enhancement for WLAN and X-Band Applications - Bal S. Virdee; Tohid Aribi; Tohid Sedghi (Micromachines)
This paper presents a novel multi-layer, dual-band antenna array designed for WLAN and X-band applications, incorporating several innovative features. The design employs a pentagon-shaped radiating element with parasitic strips to enable dual-band operation. A dual-transformed feed network with chamfered feed strip corners minimizes radiation distortion and cross-polarization while introducing orthogonal phase shifts to achieve circular polarization (CP) at the X-band. A Fabry–Pérot structure, strategically placed above the array, enhances gain in the WLAN band. The antenna demonstrates an impedance bandwidth of 1.8 GHz (S11 < −10 dB) at the WLAN band, with 36% fractional bandwidth, and 4.3 GHz at the X-band, with 43% fractional bandwidth. Measured peak gains are 7 dBi for the WLAN band and 6.8 dBi for the X-band, with favourable S11 levels, omni-directional radiation patterns, and consistent gain across both bands. Circular polarization is achieved within 8.5–10.4 GHz. Experimental results confirm the array’s significant advancements in multi-band performance, making it highly suitable for diverse wireless communication applications.